Application of UAV in agriculture: a paper review / Saiful Nizar Abd Razak and Zareen Zulkifli - Abd Razak, Saiful Nizar; Zulkifli, Zareen (Faculty of Plantation and Agrotechnology, 2018)
In this advanced era of technology, there are many machines or engineering tools that are being applied in many sector in this world especially in agriculture to easier the job that are being done. For example, the use of drone: or unmanned aerial vehicles (UA V) in agricultural sector is widely used for many purposes that can greatly benefits the farmers and plantation company or company that are practicing the agriculture. UA V is aircraft that are attached or equipped with the sensors, processing unit and communication system that are not driven as human pilot but with auto control. There are many benefits of the drone or UAV that can easier the farmer's job such as can be a method to control the pest and disease through spraying, compared to the manually spraying this method is quite effective and efficient because can cut cost and done it in short period of time. The UAV also can be used as tool of monitoring the crop for yield scout, weed scout and also pest and disease scout. It is also can be used as several types of mapping such as yield mapping. boundary mapping. Other than that it is also can be used to improve the soil sampling. So that, it is show, · that the use of UA V is to makes the improvement and precise information in agriculture in order to farmer or Agriculture based company ·will get to make quick and accurate decision to overcome the problem occurred.